Effects of Tai Chi exercise on heart rate variability - Aimee R. Cole (2018)
© 2016 Elsevier Ltd. Tai Chi is a callisthenic exercise form that incorporates aerobic exercise with diaphragmatic breathing. These two aspects alone have been shown to enhance the heart rate variability, warranting research into the effects of Tai Chi on autonomic nervous system modulation and heart rate variability. A low heart rate variability has been shown to be indicative of compromised health. Any methods to enhance the heart rate variability, in particular, non-pharmacological methods, are therefore seen as beneficial to health and are sought after. The aim of this review was to comprehensively summarize the currently published studies regarding the effects of Tai Chi on heart rate variability. Both consistent and inconsistent findings are presented and discussed, and an overall conclusion attained which could benefit future clinical studies.